Pengembangan Instrumen Evaluasi Berbasis HOTS Mata Pelajaran OTK Humas Dan Keprotokolan di SMK IPIEMS Surabaya - Yuliana Zamkakay (Universitas Negeri Surabaya, 2022)
The purpose of this research is to develop an assessment instrument based on HOTS (higher-order thinking skills). The results of the development in this study were in the form of a test instrument packaged using a google form. The method used in this study is a research and development method with the development version of Sugiyono. The subjects in this study were all students of class XI majoring in Public Relations and Protocol OTK as many as 30 students. The research instruments include interview guidelines, expert validation sheets to determine the quality of the questions, and student response sheets that were tested for quantitative and qualitative analysis. Quantitative analysis was obtained from the results of item analysis consisting of validity, reliability, level of difficulty of questions, discriminating power of questions, distractors, analysis of higher-order thinking skills and student response sheets, in qualitative analysis of test data the average percentage was 87.7% including in the